Mechanism and treatment of secondary glaucoma after corneal transplantation: a review - Lin, Yumeng; Gou, Qiaoyin; Yu, Ping; Wu, Zhengfang (Frontiers in Ophthalmology, 2024)
Corneal transplantation is a common treatment for corneal diseases. Secondary glaucoma after corneal transplantation is the second leading cause of failure of keratoplasty. This article reviews the mechanism and treatment of secondary glaucoma after corneal transplantation.